2017
DOI: 10.1093/icesjms/fsx202
|View full text |Cite
|
Sign up to set email alerts
|

Assessing causal links in fish stock–recruitment relationships

Abstract: Understanding whether recruitment fluctuations in fish stock arise from stochastic forcing (e.g. environmental variations) rather than deterministic forces (e.g. intrinsic dynamics) is a long standing question with important applied consequences for fisheries ecology. In particular, the relationship between recruitment, spawning stock biomass and environmental factors is still poorly understood, even though this aspect is crucial for fisheries management. Fisheries data are often short, but arise from complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
4
12
0
Order By: Relevance
“…In keeping with earlier results by Pierre et al. (), we find that causal coupling between stock and recruitment is fairly common (Figure ). CCM identified significant causal coupling between stock size and recruits for 107 of the 185 time series tested (Figure ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In keeping with earlier results by Pierre et al. (), we find that causal coupling between stock and recruitment is fairly common (Figure ). CCM identified significant causal coupling between stock size and recruits for 107 of the 185 time series tested (Figure ).…”
Section: Resultssupporting
confidence: 93%
“…Previous analyses based on S‐map (e.g. Deyle et al., ; Pierre et al., ) use a fixed lag for each coordinate. In particular, the time step was set to one and all lags up to E are included in the model.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the density dependence in the spawner-recruitment relationships relies on a masked density dependence in TEPPS/TEPPSW, the TEP-recruitment relationships will be weaker than the SSB-recruitment relationships. Another controversial issue is the relative roles of density-dependent (self-regulating) and density-independent (environmentally regulating) processes throughout the life stages (Andersen et al, 2017;Minto et al, 2008;Myers & Barrowman, 1996;Pierre, Rouyer, Bonhommeau, & Fromentin, 2018). Recent meta-analyses showed that the spawner-recruitment relationships were weaker than previously recognized (Cury et al, 2014;Munch, Giron-Nava, & Sugihara, 2018;Szuwalski et al, 2015).…”
Section: Discussionmentioning
confidence: 99%